(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: Due to Switzerland’s shortage of general practitioners (GPs), task shifting through interprofessional collaboration is needed to relieve GPs’ workload and allow the continued provision of quality care. The profession of specialized medical assistant (SMA) was created in Switzerland several years ago to provide a career advancement opportunity for medical practice assistants (MPAs) and intended to counteract the increasing scarcity of resources in primary care. Clinical specialized medical assistants (CSMAs) are trained to care for a set of chronic conditions, such as diabetes. OBJECTIVE: We aimed to compare the quality of care for patients with type 2 diabetes in practices with and without CSMAs. Further, we aimed to investigate whether evidence exists that CSMA care models may allow for task shifting and the provision of interprofessional care while maintaining a high quality of care and to assess patient experiences with diabetes care in both care models. METHODS: The present study was a paper-based cross-sectional survey of patient data. A total of 171 patients with type 2 diabetes who had been under the care of either a GP with CSMA (91 patients) or a GP without CSMA (80 patients) for at least one year were consecutively recruited for the study. Data were collected from mid-September 2020 to mid-June 2021. For the statistical analyses, we used descriptive statistics and t-tests. RESULTS: Patients from both practice types were comparable in age, gender and diabetes-relevant factors such as Body Mass Index, smoking status and blood pressure. Overall, patients in both models received a high quality of care (Diabetes Treatment Satisfaction Questionnaire, DTSQ >32/36 points, SGED >75 points) and a low treatment burden (Treatment Burden Questionnaire, TBQ <20/150 points). When comparing patients’ DTSQ, SGED and TBQ in both groups, we found no significant differences in diabetes-specific satisfaction (32.1 [SD 3.6] vs. 32.4 [SD 3.8], p = 0.7), SGED score (80.2 [SD 8.5] vs. 75.9 [SD 4.8], p = 0.18) or treatment burden (19.2 [SD 15.6] vs. 18.8 [SD 21.4], p = 0.89). CONCLUSION: Our comparison of patient-reported outcomes and SGED criteria of patients with type 2 diabetes in practices with and without CSMAs showed an equally high quality of care and a low treatment burden. More research is needed on the long-term effects and benefits of the care provided by CSMAs and which other tasks could be shifted to CSMAs to reduce the burden on GPs in the future. At the same time, an increasing number of patients with type 2 diabetes will require high-quality primary care.